2017
DOI: 10.1002/2211-5463.12276
|View full text |Cite
|
Sign up to set email alerts
|

Mouse glutamate carboxypeptidase II (GCPII) has a similar enzyme activity and inhibition profile but a different tissue distribution to human GCPII

Abstract: Glutamate carboxypeptidase II ( GCPII ), also known as prostate‐specific membrane antigen ( PSMA ) or folate hydrolase, is a metallopeptidase expressed predominantly in the human brain and prostate. GCPII expression is considerably increased in prostate carcinoma, and the enzyme also participates in glutamate excitotoxicity in the brain. Therefore, GCPII represents an important diagnostic marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…On the other hand, the amount of PSMA/GCPII in the epididymis was as high as 180 pg per 1 μg total protein. In comparison, we previously showed that the amount of PSMA/GCPII in the male kidney and brain is 100‐250 pg and 2.5‐10 pg in 1 μg total protein, respectively . We thus visualized and localized PSMA/GCPII in the epididymis by immunohistochemistry using two different antibodies against mouse PSMA/GCPII—GCPII‐02 and GCPII‐04 (Figure ).…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…On the other hand, the amount of PSMA/GCPII in the epididymis was as high as 180 pg per 1 μg total protein. In comparison, we previously showed that the amount of PSMA/GCPII in the male kidney and brain is 100‐250 pg and 2.5‐10 pg in 1 μg total protein, respectively . We thus visualized and localized PSMA/GCPII in the epididymis by immunohistochemistry using two different antibodies against mouse PSMA/GCPII—GCPII‐02 and GCPII‐04 (Figure ).…”
Section: Resultsmentioning
confidence: 84%
“…The extracellular portion of mouse GCPII (rm‐GCPII) was prepared as previously described . Briefly, large scale expression was performed using Drosophila S2 (BiP‐BirA‐KDEL) cells stably transfected with a plasmid encoding rm‐GCPII (pMT/BiP/AvimGCPII) . Biotinylated rm‐GCPII was purified from S2 cell media using Streptavidin Mutein Matrix (Roche, Basel, Switzerland) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations